Representasi Alam Etnis Suku Lauje Sulawesi Tengah dalam Novel Di Balik Kabut Gunung Sojol Karya Moh. Rifai M. Hadi: Tinjauan Ekokritik - A. Sanaul Hasanah; Nensilianti Nensilianti; Suarni Syam Saguni (Universitas Negeri Makassar, 2022)
Abstract: This research purposes to describe nature which is represented of Lauje ethnicity Central Sulawesi based on the ecocritic study Glotfelty. This research uses the qualitative research method. Data of this research is written text from the novel di Balik Kabut Gunung Sojol by Moh. Rifai M. Hadi describes the represented nature. Source of this research data is novel di Balik Kabut Gunung Sojol by Moh. Rifai M. Hadi. The data collection techniques of this research are literature study techniques including reading, understanding, data corpus, and data analysis. This research analysis makes to identify, classify, analyze, and describe the nature which is represented Di Balik Kabut Gunung Sojol by Moh. Rifai M. Hadi. The results of the analysis indicate that the novel Di Balik Kabut Gunug Sojol reveals the representation of nature. The natural representation consists of natural damage and the natural beauty of Mount Sojol. The natural damage is in the form of tree cutting, rare plants, animal extinction, climate, and pollution. The natural beauty of the mountainous background is marked by depictions of nature in the form of rivers, trees, fog, and beaches.Keywords: Representation, novel, ecocritic.